The anti-social network: cyberstalking victimization among college students - Reyns, Bradford W. (Criminal justice: recent scholarship, 2012)
The problem of cyberstalking -- Lifestyle-routine activities theory -- The theoretical transition to cyberspace -- Researching the problem of cyberstalking -- The extent and nature of cyberstalking victimization -- Summary, implications, and the future of cyberstalking research